Interno borghese anni cinquanta: Quaderno proibito di Alba de Céspedes al crocevia di generi romanzeschi (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2016)
The article proposes an analysis of the third novel of Alba de Céspedes, Quaderno proibito (1952).. Particular attention is devoted to the publication of the work, in serial form, in a very popular magazine: a choice read as a symptom of the author’s will of communicatig with a wide and sexually connoted audience. We thus analyze the structure of the novel, detecting both the constructive strategies designed to tune in to the wide audience of ‘she’ readers, both references to different genres (Diary Familienroman, Bildungsroman, sentimental novel, social novel) that de Céspedes exploits to give aesthetic force to her message.